Histopathological and ultrastructural effects of methyl parathion on rat testis and protection by selenium - Mohamed SA. El-Gerbed (Journal of Applied Pharmaceutical Science, 2013)
The present study was conducted to evaluate the possible protective effect of selenium in reversing methyl parathion -induced testicular damage in male rats, using light and electron microscopy with reference to plasma testosterone (T) and lutenizing hormone (LH) levels. The animals were randomly divided into four groups, Group 1: control animals. Group 2: animals were treated with sodium selenite in a dose (10µg/kg b.w). Group 3: rats were given methyl parathion in a dose (0.28 mg/kg b.w). Group 4: rats were received sodium selenite prior to treatment with methyl parathion. Results showed that animals exposed to methyl parathion displayed a reduction in body and testicular weight and a reduction in seminiferous tubules diameter. At the end of the treatments plasma testosterone and LH concentrations were reduced significantly in methyl parathion-treated rats. Light and electron microscopy of testes from treated animals with methyl parathion showed disorganization of tubular elements with increased intercellular space. Also, revealed necrosis and cellular damage. In addition, a significant increase in sperm DNA fragmentation was detected. Selenium supplementation to rats given methyl parathion improved the testicular damage. In conclusion, Selenium may be useful for the prevention and treatment of methyl parathion -induced testicular damage.
Keywords: Methyl parathion, Selenium, Testicular damage, TUNEL